Effectiveness of Sambiloto Leaf Infusion (Andrographis paniculata Nees.) as an Antidiarrheal in Mice (Mus musculus) - Anggraini, Lutvi; Mustika, Aulia Andi; Priosoeryanto, Bambang Pontjo; Sutardi, Lina Noviyanti (Jurnal Jamu Indonesia, 2025)
Sambiloto is one of the most diverse herbal plants. The active content found in sambiloto is believed to fight diseases, one of which is diarrhea. This study aimed to determine the content of secondary metabolite compounds with phytochemical tests, the antidiarrheal effectiveness of sambiloto leaf infusa using the intestinal protection method, and the effective concentration of antidiarrheal in mice. This study used 25 mice, which were divided into five groups: control (+), control (-), and three treatment groups of sambiloto leaf infusa with concentrations of 25%, 50%, and 100% given orally. The results of phytochemical tests of sambiloto that have the potential to be antidiarrheal compounds are alkaloids, flavonoids, steroids, terpenoids, saponins, and tannins. The parameters observed were the frequency of defecation and consistency of mice's feces every 30 minutes for 9 hours. The results of this study showed that bitter melon leaf infuse preparations at concentrations of 25%, 50%, and 100% had antidiarrheal activity, with the best antidiarrheal activity shown at a concentration of 25%.